Tantangan Implementasi Kebijakan Zero Waste di Kabupaten Tulungagung: Studi Pada Sistem Pengelolaan Sampah Rumah Tangga - Sheffia Dwi Cahyanti; Tarissa Putri Zahrani; Fikri Syahri Alianfa; Nunun Nurhajati (STISIP Margarana, 2026)
The increasing volume of household waste in Tulungagung Regency is an environmental issue that requires effective and sustainable policy management. The local government has implemented a Zero Waste-based waste management policy through the 3R approach (Reduce, Reuse, Recycle), but its implementation has not shown optimal results. This study aims to examine the various challenges in implementing the Zero Waste policy in the household waste management system in Tulungagung Regency. The method used was descriptive qualitative research with a literature approach (library research) sourced from laws and regulations, government policy documents, official reports from relevant agencies, and scientific journal articles. Data analysis was conducted using George C. Edwards III's policy implementation theoretical framework, which encompasses aspects of communication, resources, implementer disposition, and bureaucratic structure. The results indicate weak policy communication, limited supporting facilities and infrastructure, low community participation, and suboptimal bureaucratic coordination between relevant institutions. Therefore, strengthening policy communication, improving the quality of facilities and infrastructure, community empowerment, and improving institutional coordination are needed to support the realization of sustainable household waste management.